Status Gizi Penderita Hipertensi di Wilayah Kerja Puskesmas Kinilow Tomohon - Ester Candrawati Musa (Sam Ratulangi Journal of Public Health, 2021)
Background: Hypertension is one of the health problems in Indonesia, especially the City of Tomohon. The prevalence of hypertension continues to increase every year. The death rate due to hypertension is quite high. One of the risk factors for hypertension is excess nutritional status. The purpose of this study was to describe the nutritional status of hypertension sufferers in the working area of the Puskesmas Tinoor, Tomohon City. Methode: This is a descriptive research. This is research was carried out in the working area of the Puskesmas Tinoor, Tomohon City in October-December 2021. A total of 72 hypertension patient were the subjects in this study. The instrument of this research is the filling sheet. Data were analyzed univariately. Result: The results showed that the average body weight (BW) was 66.6 kg, the median was 66 kg with a range of 43-120 kg. Based on height (BH) obtained an average of 162.3 cm, median 165 cm with a range of 142-181 cm. Based on the body mass index (BMI), the average BMI was 25.33, the median was 24.8 with a range of 17.2-42.1. Conclusion: That can be conclude that the average nutritional status of hypertension sufferers in the working area of the Puskesmas Tinoor, Tomohon City, is in the pre-obesity category. Therefore, patients can make efforts to maintain an ideal BMI through physical activity and regulating food intake.